Expression of PDL-1 and Its Correlation with TIL in Triple Negative Cases of Breast Carcinoma - Sharma, Neha; Singh, Akashdeep; Kaur, Arshdeep; Manjari, Mridu (Annals of Pathology and Laboratory Medicine, 2021)
Background: In the present study, we aimed to determine the expression of PDL1 and its correlation with TIL in Triple Negative (ER, PR and Her 2neu negative) cases of breast carcinoma (immune-histochemical study) Methods: Expression of PD-L1 was seen on 40 proven triple negative cases of breast carcinomas (TNBC) and to correlate it with other parameters affecting prognosis of the disease. All the cases were infiltrating ductal carcinoma NOS (not otherwise specified) Result: Maximum cases were Grade III (67.5%) followed by Grade II (32.5%). PD-L1 positivity was seen in 32.5% cases whereas TIL was positive for PD-L1 in 27.5 %. 5 cases were positive for both epithelial cell and TIL. Out of 13 PD-L1 positive tumors, 38.5% cases showed TIL positivity whereas out of 27 PD-L1 negative tumors, only 22.2% were TIL positive. PD-L1 expression in TIL was seen in 38.5% of cases however there was no statistically significant correlation between PD-L1 positivity and TIL positivity. PDL-1 positivity was more in Grade III (33.3%) as compared to Grade II (23%) lesions. Thus, it was observed that PD-L1 positivity increased from grade II to grade III lesions. Conclusion: Intra-tumoral expression of PD-L1 is directly proportional to histological grade, aggressive subtypes in TNBC cases however there was no statistically significant correlation between PD-L1 positivity in tumor cells and TIL positivity. We thus postulate that measurement of PD-L1 expression in TNBC cases could enhance the accuracy of predicting patient prognosis and allow for optimal treatment selection.